Corporate Education: Communication Competence (Interdisciplinary Studies Journal, 2021)
This study aimed to analyze corporate education, focusing on communication and the strategies that organizations adopt to disseminate knowledge, policies, and guidelines. A qualitative research was conducted with 54 participants, based on bibliographies and field research, contributing to the reflection on Corporate Education and the development of communication competence. Finally, it was concluded that there is a challenge to be faced regarding communication strategies and tactics, aiming at the implementation of initiatives for the improvement of this competence.
Keywords: Corporate education; Competence; Communication